Utilization of mouthguard among school children in Saudi Arabia: Utilization of mouthguard among school children in Saudi Arabia - Alomar, Mohammad Saad (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Aim: To evaluate children's attitude towards mouthguard utilization among the school children.Methods: This cross-sectional study was conducted among children between 8 to 16 years of both genders in students attending the school in Riyadh, Saudi Arabia. A structural questionnaire was prepared, consisting of the questions related to the demographic details, attitude, and conception of the children toward using a mouthguard. The questionnaire was sent to the school teachers to distribute among the respective school children. Descriptive statistics were used to analyse the data.Results: A total of 1116 children completed the survey form, of which 488 were females and 628  males. The prevalence of mouthguard use among Saudi school children was found to be 3.32%. Out of the total study subjects, 72.68% of the subjects believed that mouthguards could protect them from injuries. The most common reason for not wearing mouthguards was that they never thought about it (38.47), children felt not necessary (30.58%), being expensive(11.02%), and 19.93% of subjects never had any injury. Out of 37, 2 subjects never experienced problems with the mouthguards. The most common problems with mouthguards were Difficulty in speech, being uncomfortable and expensive, followed by interference with breathing Conclusion: Prevalence of mouthguard use was 3.32% in Saudi school children aged between 8-16 years. The most common reason for not using it was a lack of knowledge. Counseling the young children interested in sports activities is the need of an hour.